Microstructural development and effect of different Cu/C contents on dimensional changes during sintering of PM steels. (December 2015) - Bilbao, C.; Sainz, S.; Veiga, A.; Castro, F.
Abstract : Powder blends within the Fe–Cu–C system are extensively used by the Powder Metallurgy industry. Based on the optimisation of mechanical properties the purpose of this work is to further understand the dimensional changes produced in the powder compact during sintering. Green compacts containing copper and carbon within ranges 0.5–3.5%Cu and 0.3–0.9%C were die pressed and sintered under different conditions varying processing parameters, including compaction pressure, temperature and time. Better understanding of the effect of different Cu/C combinations on dimensional changes was approached using the results obtained from dilatometry studies combined with interrupted sintering experiments. For selected specimens the effect of elemental Ni additions, at 1 and 4%, on dimensional changes was studied along with a detailed description of microstructural development. It was clearly observed that swelling due to copper melting and grain boundary diffusion is diminished as graphite additions were increased. The impact of Cu–C–Ni additions on hardness was also evaluated.